Using Truncated Data Sets in Spherical-Scanning Antenna Measurements - Ronald C. Wittmann; Carl F. Stubenrauch; Michael H. Francis (International Journal of Antennas and Propagation)
We discuss the mitigation of truncation errors in spherical-scanning measurements by use of a constrained least-squares estimation method. The main emphasis is the spherical harmonic representation of probe transmitting and receiving functions; however, our method is applicable to near-field measurement of electrically small antennas for which full-sphere data are either unreliable or unavailable.